Love across borders and travel bans: for the love of her and love of the United States - Downing Bice, Channing, author (Colorado State University. Libraries, 2017)
7,500 miles; seven Muslim majority countries; six embassies; five years; three career changes; two people; one proxy marriage. As if straight out of a movie or TV series, this project explores a five-year love story with one major hurdle; United States Immigration Laws and their many intricacies. However, this isn't television, lives are put on hold, either temporarily or permanently, and loved ones can be separated based on legislative laws and executive orders. After interviewing M and his wife and hearing the many hurdles the couple faced to get their education, get married, and trying to start a new career path in line with public policy and immigration laws; I wanted to examine the relationship between public policy, propaganda, and the psychological stressors of migration. This research is in conjunction with the 2012 Iranian Sanctions, 2017 travel ban and Muslim-American immigrants, but could have implication for other races or ethnicities trying to immigrate to the United States.
090 - Channing Faith Downing Bice
Keywords: travel bans; immigration; sanction; immigrant; Muslim; Muslim-American; psychological; legislative; public policy; propaganda